A Wavelet Algorithm for Fourier-Bessel Transform Arising in Optics. (31st August 2015) - Irfan, Nagma; Siddiqi, A. H.
Abstract : The aim of the paper is to propose an efficient and stable algorithm that is quite accurate and fast for numerical evaluation of the Fourier-Bessel transform of orderν,     ν > - 1, using wavelets. The philosophy behind the proposed algorithm is to replace the partt f ( t ) of the integral by its wavelet decomposition obtained by using CAS wavelets thus representingF ν ( p ) as a Fourier-Bessel series with coefficients depending strongly on the input functiont f ( t ) . The wavelet method indicates that the approach is easy to implement and thus computationally very attractive.